1965
DOI: 10.1002/jsfa.2740160801
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of leaf protein concentrates determined in biological tests with rats and by microbiological methods

Abstract: The biological values and true digestibilities of a number of leaf protein concentrates have been determined by the balance-sheet method a t an 8% level of protein intake on young growing rats. Determinations were made on preparations from the leaves of 14 different species of plants. The effects of several methods of drying the concentrates and of the maturity of the leaves at harvesting were studied. The availability of some essential amino-acids was determined microbiologically in selected samples; in all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…A second approach consists in directly supplementing the incomplete plant protein with the necessary amino acid. Supplementation of LPC using methionine has been successfully performed to improve the actual dietary quality of the protein, for instance in the case of alfalfa protein concentrate (Hanczakowski et al, 1991), while similar lysine or isoleucine (Henry and Ford, 1965) supplementations have not lead to special improvement. Nonetheless, with respect to the second case, it has been pointed out that in vivo experiments on rats may differ from the situation found in the human body due to the higher methionine demand of these animals (Byers, 1971).…”
Section: Difference In Nutritional Value Of Green and White Proteinmentioning
confidence: 99%
“…A second approach consists in directly supplementing the incomplete plant protein with the necessary amino acid. Supplementation of LPC using methionine has been successfully performed to improve the actual dietary quality of the protein, for instance in the case of alfalfa protein concentrate (Hanczakowski et al, 1991), while similar lysine or isoleucine (Henry and Ford, 1965) supplementations have not lead to special improvement. Nonetheless, with respect to the second case, it has been pointed out that in vivo experiments on rats may differ from the situation found in the human body due to the higher methionine demand of these animals (Byers, 1971).…”
Section: Difference In Nutritional Value Of Green and White Proteinmentioning
confidence: 99%
“…The nutritional qualites of the plant juice and the protein‐rich concentrate for monogastrics have been evaluated in earlier studies focusing mainly on chickens, pigs or rats; however, the results obtained are not consistent. Some studies have demonstrated an improved growth of rats, as well as improved performance, weight gain and meat quality of pigs, when they are fed with plant juice or plant protein concentrate, whereas other studies have reported the opposite . An improper processing of plant material has been suggested to be one cause of the inconsistency in protein quality, but improvements in methods for green plant processing and protein extraction, combined with the increasing need for animal protein fuel new attempts to produce high‐quality protein alternatives to soy protein for animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, which has 260000 ha under sugar beet cultivation, it is estimated that some 2 Mt of waste foliage (crude protein content 30g kg-' fresh weight) could yield 60 kt protein. Large proportions of sugar beet leaf protein have been isolated as a green concentrate (Carlsson 1983;Shah 1983) of acceptable nutritive value (Henry and Ford 1965;Subba Rau et a1 1972) but protein concentrates obtained after separation of the chlorophyllcontaining protein may be more acceptable for human consumption (Heath 1977;Pirie 1980). However, separation of the chlorophyll-containing fraction usually results in only a small yield of white protein in the second stage precipitation.…”
Section: Introductionmentioning
confidence: 99%